2014
DOI: 10.1515/epoly-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(vinyl chloride-graft-2-vinylpyridine) graft copolymers using a novel macroinitiator by reversible addition-fragmentation chain transfer polymerization

Abstract: Synthesis of poly(vinyl chloride-graft-2-vinylpyridine) graft copolymers was carried out by reversible addition-fragmentation chain transfer (RAFT) polymerization of 2-vinylpyridine using a novel macroinitiator (RAFT macroinitiator). For this purpose, RAFT macroinitiator was obtained from the potassium salt of ethyl xanthogenate and poly(vinyl chloride) (PVC). Then the graft copolymers were synthesized by using RAFT macroinitiator and 2-vinylpyridine. The principal parameters such as monomer concentration, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…4VP‐ g ‐DPNR exhibited two different T g values at −64.1 and 139.5 °C. This suggested that 4VP‐ g ‐DPNR comprised both NR and 4VP domains, and that the graft copolymer remained largely amorphous …”
Section: Resultsmentioning
confidence: 99%
“…4VP‐ g ‐DPNR exhibited two different T g values at −64.1 and 139.5 °C. This suggested that 4VP‐ g ‐DPNR comprised both NR and 4VP domains, and that the graft copolymer remained largely amorphous …”
Section: Resultsmentioning
confidence: 99%
“…Purification of PVC PVC was purified as the cited literature [18] as follow; 30 g of it was solved in 120 mL of THF in 24 hours, and precipitated in methanol and dried under vacuum at 45 o C for 24 hours before use.…”
Section: Instrumentationmentioning
confidence: 99%
“…Fractional precipitations (γ) of the polymers were determined by following to the process stated in the literatures (Öztürk et al 2014, Hazer et al 1994, Öztürk et al 2011. Vacuum dried polymer sample (about 0.1 g) was dissolved in 10 mL THF.…”
Section: Fractional Precipitation Of the Graft Copolymersmentioning
confidence: 99%